2017
DOI: 10.1039/c6nj04030f
|View full text |Cite
|
Sign up to set email alerts
|

An environmentally benign one pot green synthesis of reduced graphene oxide based composites for the enzyme free electrochemical detection of hydrogen peroxide

Abstract: An rGO/Ag–Pd nanocomposite prepared by using Arachis hypogaea scrap extract was exploited as an enzyme-free electrochemical probe for the detection of H2O2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The peaks at about 40.15°, 46.61°, 68.19° and 82.3° corresponded to the (111), (200), (220) and (311) lattice planes of the fcc crystalline structure of Pd, respectively . The peaks at 38.16°, 44.42°, 64.5°and 77.53° were assigned to the (111), (200), (220) and (311) crystalline planes of cubic Ag, respectively . This result indicated that Pd‐Ag bimetallic nanoparticles supported on graphene (Pd‐Ag/rGO) was formed.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The peaks at about 40.15°, 46.61°, 68.19° and 82.3° corresponded to the (111), (200), (220) and (311) lattice planes of the fcc crystalline structure of Pd, respectively . The peaks at 38.16°, 44.42°, 64.5°and 77.53° were assigned to the (111), (200), (220) and (311) crystalline planes of cubic Ag, respectively . This result indicated that Pd‐Ag bimetallic nanoparticles supported on graphene (Pd‐Ag/rGO) was formed.…”
Section: Resultsmentioning
confidence: 85%
“…24 The peaks at 38.16 ∘ , 44.42 ∘ , 64.5 ∘ and 77.53 ∘ were assigned to the (111), (200), (220) and (311) crystalline planes of cubic Ag, respectively. 25 This result indicated that Pd-Ag bimetallic nanoparticles supported on graphene (Pd-Ag/rGO) was formed.…”
Section: Characterization Of Pd-ag/rgomentioning
confidence: 96%
“…These polymers are admirable platforms for the electrochemical sensing applications of ascorbic acid . In recent literature, electrochemical sensors became available for detection of glucose, hydrogen peroxide, dopamine and ascorbic acid (AA) …”
Section: Introductionmentioning
confidence: 99%
“…Thus, H 2 O 2 determination is gaining more attention in the biomedical science, food inspection and industrial application as a countermeasure in preventing further damage on life and property. Various analytical methods, such as colorimetric , fluorescence , titrimetric , chemiluminescence , chromatography and electrochemical , have been established for detection and quantification of H 2 O 2 . Among these techniques, electrochemical detection has many advantages such as simple instrumentation, reliability, excellent sensitivity and selectivity and rapid response time.…”
Section: Introductionmentioning
confidence: 96%